Use of generic medicines in Latvia: awareness, opinions and experiences of the population - Ieva Salmane Kulikovska; Elita Poplavska; Marija Ceha; Signe Mezinska (Taylor & Francis Group, 2019)
Background To stimulate use of generic medicines a combination of supply and demand side mechanisms are employed in the Latvian reimbursement system. It is reported that patients have high out-of-pocket pharmaceutical spending and that they overpay by not choosing generic medicines. Patient preferences may be an important obstacle in implementing generic policy. Objective of this study was to assess awareness, opinions and experience of the Latvian population regarding use of generic medicines. Methods Survey of representative sample of the population of Latvia (n = 1005) aged 18-74 was conducted in March 2015. The survey was distributed in Latvian and Russian languages using Computer Assisted Web Interviews. Associations between experience with generic medicines, preference for medicines, and sociodemographic variables were tested with Pearson Chi-square statistics. Associations between the previous experience and information given by different sources versus choice between medicines were tested with Spearman's correlation test. Results 72.3% of the population were informed about generic medicines. Men (66.9%) and respondents with primary or secondary education (58.3%; 69.3%) were less informed compared to total (72.3%). From those who recalled using generic medicines (n = 441), 94.4% evaluated their experience as positive or neutral. Despite this, only 21% of the population would opt for generic medicines. The strongest preference for brand-name medicines was in the age group > 55 (40.5%). Opinion of a physician was the most important factor when choosing between generic and brand-name medicines (88.7%). The more positive the information provided by general practitioners, physician specialists, pharmacists, family members, friends and internet is perceived, the more likely respondents are to choose generic medicines (p < 0.001). Conclusion This study demonstrates that people in Latvia are aware of generic medicines but only a minority of the population would choose them when presented with a choice. It is therefore important that health care professionals provide objective and unbiased information about generic medicines to their patients. Interventions should aim to reach groups that are less informed and to improve providers' understanding and communication with patients about generics.